Biodiversity assessment of invertebrates in hill streams at Bukit Timah nature reserve. - Lim, Jing Yang. (2012)
Bukit Timah Nature Reserve (BTNR) contains the largest patch of primary rainforest over the last century. To date, little data has been collected detailing the population dynamics and abundance of the invertebrate species residing in the hill streams of BTNR. Through both hand and trap sampling techniques, fauna present were mapped and identified and traced to their respective streams. Using the same sampling methods, a baseline population abundance of the species residing in 4 streams selected to represent BTNR was obtained. The Shannon Index revealed that Lasia stream had the greatest biodiversity. Numerical dominance of M. malayanum was observed where it outnumbered all other species in the streams where it was found from 184 individuals in Lasia to 507 in Fern Valley. Lasia stream also experienced invasion of 2 non-native species of waterstriders previously not known to exist in BTNR. Fern Valley was found to contain a thriving community of J. singaporensis and Dairy Farm was found to have a significant difference in abundance of P. maculata compared to Lasia. Results obtained will serve as a baseline to help facilitate future conservation efforts in this area. Further monitoring is needed to follow up after this study.